2007
DOI: 10.1128/jvi.01785-06
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Amphipathic Peptide of Semliki Forest Virus Replicase Protein nsP1 in Membrane Association and Virus Replication

Abstract: Semliki Forest virus RNA replication takes place in association with specific cytoplasmic vacuoles, derived from the endosomal apparatus. Of the four virus-encoded replicase proteins, nsP1 serves as the membrane anchor of the replication complex. An amphipathic peptide segment, G 245 STLYTESRKLLRSWHLPSV 264 , has been implicated in the membrane binding of nsP1. nsP1 variants with changes within the peptide were studied after protein expression and in the context of virus infection. Proteins with mutations R253… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
108
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(117 citation statements)
references
References 50 publications
(59 reference statements)
8
108
0
1
Order By: Relevance
“…Recent research on two members of the Alphavirus-like superfamily, Semliki Forest virus (SFV, genus Alphavirus; family Togaviridae) and brome mosaic virus (BMV, genus Bromovirus, family Bromoviridae), has revealed that the MTR domain contains sequences responsible for punctate structure formation (den Boon et al, 2001;Spuul et al, 2007;Liu et al, 2009). Because GRSPaV also belongs to the Alphavirus-like superfamily, we predicted that the MTR domain of its replicase polyprotein might also contain sequences capable of forming punctate bodies in plant cells.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent research on two members of the Alphavirus-like superfamily, Semliki Forest virus (SFV, genus Alphavirus; family Togaviridae) and brome mosaic virus (BMV, genus Bromovirus, family Bromoviridae), has revealed that the MTR domain contains sequences responsible for punctate structure formation (den Boon et al, 2001;Spuul et al, 2007;Liu et al, 2009). Because GRSPaV also belongs to the Alphavirus-like superfamily, we predicted that the MTR domain of its replicase polyprotein might also contain sequences capable of forming punctate bodies in plant cells.…”
Section: Resultsmentioning
confidence: 99%
“…To test if the replicase polyprotein of GRSPaV contains a functionally similar amphipathic a-helix sequence involved in forming punctate structures and in membrane association, we first performed hydropathy analyses of the MTR domain using the Protean program (DNASTAR), which revealed several candidate regions. The region encompassing amino acid residues 165-187 (PRVISTGARNLFLHDEIHYWSIS) seemed to be the most promising for further analyses, in part because it had a sufficient length to allow formation of an amphipathic a-helix as hypothesized to be an IPM anchor for monotopic membrane association in SFV (Spuul et al, 2007). Importantly, key amino acid residues that are consistently identified in IPM anchors, namely R, F and W (Sapay et al, 2006), are also present in this region.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations